266=-7(-7x+11)

Simple and best practice solution for 266=-7(-7x+11) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 266=-7(-7x+11) equation:


Simplifying
266 = -7(-7x + 11)

Reorder the terms:
266 = -7(11 + -7x)
266 = (11 * -7 + -7x * -7)
266 = (-77 + 49x)

Solving
266 = -77 + 49x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-49x' to each side of the equation.
266 + -49x = -77 + 49x + -49x

Combine like terms: 49x + -49x = 0
266 + -49x = -77 + 0
266 + -49x = -77

Add '-266' to each side of the equation.
266 + -266 + -49x = -77 + -266

Combine like terms: 266 + -266 = 0
0 + -49x = -77 + -266
-49x = -77 + -266

Combine like terms: -77 + -266 = -343
-49x = -343

Divide each side by '-49'.
x = 7

Simplifying
x = 7

See similar equations:

| x+15=7x-9 | | 4n=944 | | 4=x/13+1 | | 7x+3y=37 | | 4a+3=6a+12 | | 23=-1+6(3x-2) | | 7n-4n+11n= | | 4x+21=5x+10 | | 8(3)=v | | 11c+21=-24 | | 4(cos^2)x+7(sinx)-7=0 | | -8(4+4n)=-288 | | 4(cos^2)x+7sinx-7=0 | | -39+7k=2(7k+3)+2k | | 53=-2-(1-7n) | | 3*x+3=30 | | 50y+25x= | | y=-2x+22 | | 29t=319 | | 17+x=18*x | | 2(x+8)+7=43 | | x^3-12x^2+35= | | -6=-(p-1) | | 4p-8p+4p+6= | | 0=1960t-4.9t^2-h | | 9+(-2-8)=X | | x^2+44+16x=180 | | X^2-8x+10= | | 9=1+8(1+n) | | (W-2)(w+7)= | | 5(3+5x)=-85 | | 3y+2=-2y-7 |

Equations solver categories